New Zealand nursing students' perceptions of biosciences: A cross-sectional survey of relevance to practice, teaching delivery, self-competence and challenges. (August 2019) - Montayre, Jed; Dimalapang, Eliazar; Sparks, Trena; Neville, Stephen
Abstract: Background: Bioscience subjects are one of the most discussed nursing curricula contents in terms of the longed known teaching and learning challenges for nursing students. Recent studies examined the specific use of technology as teaching strategies. However, there are still significant gaps around nursing students' perception of biosciences within nursing education and the significance of teaching delivery methods to these perceptions. Objective: The study examined students' overall perception of biosciences within New Zealand undergraduate nursing programmes in terms of relevance to practice, teaching delivery, self-competence and challenges encountered. Method: A descriptive, cross-sectional survey design on perceptions of New Zealand nursing students on biosciences was undertaken. Results: Five hundred and forty students were included. Fifty-five percent (55%) preferred biosciences papers be taught classroom – based but using a blended learning delivery instead of an exclusively traditional classroom setting (55% vs. 21%). Perception towards the biosciences was positive and the mean perception of older students and those in Year 3 was higher compared to the other students. Overall, students believed biosciences had relevance to the practice of nursing. Conclusion: Positive perceptions of bioscience become more evident when nursing students reach their final year in the nursing programme. The contemporary profile (age) of students studying nursing are sensitive to their preferred teaching delivery. A fully online teaching approach to biosciences for nursing students will most likely require a robust approach and careful decision making for implementation.